Prevalence of Depression, Anxiety, OCD, and Social Isolation Among Married Men with Type II Diabetes - Ahmed Bilal, Iram Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This paper is a report of a study conducted to examine the prevalence of common mental disorders among a sample of married men with type II diabetes. Background. Low educated, financially constrained men are disproportionately affected by diabetes and are more likely to suffer decreased quality of life, marital and sexual satisfaction and to have co-morbidities. They are also likely to suffer more from common mental disorders due to various facets of their ailments. Method. A cross-sectional survey study with 210 married men with type II diabetes were recruited from General Hospital, Lahore between from July 2021 to August 2022. Results: Men between the ages of 26-39 report disproportionally more depression and mental health issues as compared to older demographics with diabetes. Lack of education and high HbA1c have increased prevalence. Conclusion: There is a need to explore mental health issues of men more and physicians should look into the reasons for high HbA1c and prepare diabetes learning material. Keywords: Depression, Anxiety, OCD, Type II Diabetes.